Linguistic Accessibility in Public Safety Communication: A Comparison of the Finnish and English Versions of the SPEK Website - Laine, Veera (My University, 2026)
This thesis examines how linguistic accessibility is implemented on multilingual websites, focusing on the Safety section of the Finnish National Rescue Association (SPEK) website. The central research question is whether the English version provides functionally equivalent access to safety information as the Finnish version, and how translation and localization choices might affect the user experience. The data consists of the Finnish and English versions of the Safety section, which are analyzed using a qualitative comparison based on three categories: Completeness and Consistency, Clarity and Comprehensibility, and Cultural and Informational Accessibility. The results show that the English version communicates the key safety instructions, but reduces supporting explanations, contextual information, and some structural elements. Functional equivalence is achieved at a general level, although not in all dimensions of linguistic accessibility. These results support the view that linguistic accessibility is a multidimensional concept that encompasses completeness, clarity, and cultural adaptation. The analysis also highlights the role of translation and localization practices and shows that English-language content primarily functions as a selectively adapted and condensed version of the Finnish source, reflecting institutional priorities and resource allocation rather than providing full and equal access to the content. This thesis provides practical insights into multilingual online communication in the public sector and highlights the need to combine translation practices with cultural adaptation to ensure user-centered linguistic accessibility. It contributes to translation research and public safety communication by demonstrating how language, localization, and institutional choices shape access to essential information.
Keywords: linguistic accessibility; multilingual websites; safety communication; public safety; localization; translation